Molecular modeling of layered double hydroxide intercalated with benzoate, modeling and experiment - Kovár, Petr; Pospísil, M; Nocchetti, M; Capková, P; Melánová, Klára (Journal of molecular modeling, 2007)
The structure of Zn4Al2 Layered Double Hydroxide intercalated with benzencarboxylate (C6H5COO-) was solved using molecular modeling combined with experiment (X-ray powder diffraction, IR spectroscopy, TG measurements). Molecular modeling revealed the arrangement of guest molecules, layer stacking, water content and water location in the interlayer space of the host structure. Molecular modeling using empirical force field was carried out in Cerius(2) modeling environment. Results of modeling were confronted with experiment that means comparing the calculated and measured diffraction pattern and comparing the calculated water content with the thermogravimetric value. Good agreement has been achieved between calculated and measured basal spacing: d(calc) = 15.3 A and d(exp) = 15.5 A. The number of water molecules per formula unit (6H2O per Zn4Al2(OH)12) obtained by modeling (i.e., corresponding to the energy minimum) agrees with the water content estimated by thermogravimetry. The long axis of guest molecules are almost perpendicular to the LDH layers, anchored to the host layers via COO- groups. Mutual orientation of benzoate ring planes in the interlayer space keeps the parquet arrangement. Water molecules are roughly arranged in planes adjacent to host layers together with COO- groups.
Keywords: kyselina benzoová; Spectrophotometry, Infrared; anionty; vazebná místa; Aluminum; difrakce rentgenového záření; krystalizace; hliník; Hydroxides; kyseliny karboxylové; benzen; Benzoic Acid; Magnesium Hydroxide; Benzene; molekulární modely; hydroxidy; Models, Molecular; Binding Sites; X-Ray Diffraction; Crystallization; hydroxid hořečnatý; Anions; Carboxylic Acids; Aluminum Hydroxide; zinek; spektrofotometrie infračervená; hydroxid hlinitý; Zinc